Pendampingan Proses Produksi Pembuatan Tempe Kedelai - Bernadhi, Brav Deva; Sukendar, Irwan; Rochman, Isyhad Kabirur (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Plompong Village is a village located in Sirampog District, Brebes Regency. The distance from Sultan Agung Islamic University to Plompong village is approximately 235 km. Most of the population in Plompong Village work in agriculture, so that agriculture is quite developed. Most of the crops grown on agricultural land are rice, corn and soybeans. There is 1 group that opened a tempe-making business even though the business is still a small business. The Mandiri Sejahtera Bersama Business Group is a group formed by residents of the Cirendu hamlet, Plompong village to try to produce soybean tempeh production. Tempe production also cannot be done every day due to unstable or uncertain availability of production equipment and results from soybean farming (raw materials). Production still uses manual methods to process soybean tempeh so that the resulting production cannot be done every day and the average production yield is 60 to 100 packs. Community service program in the form of mentoring the soybean tempeh production process in the Mandiri Sejahtera Bersama business group.